Osteosarcoma of the Skull: An Unusual Presentation in the Left Parietal-Occipital Region - Aditya Adhav; Sagar Bhalerao; Rajnish Nagarkar; Sirshendu Roy; Samadhan Pawar (Academia Anatomica International, 2019)
Osteosarcoma (OS) is an uncommon primary malignant brain tumor. The incidence of osteosarcoma of the skull is low with an estimated 3.4 cases per million reported per year. We report a case of OS of the skull in an 18-year-old female patient. She had complained of swelling on the left side of the head accompanied with frequent headache and diminished vision in the left eye. An PET-CT of the skull revealed a large 93x90 mm lesion in the left parietal-occipital region. Osteoblastic osteogenic sarcoma of the skull was confirmed histopathologically. The patient received six cycles of Adriamycin and cisplatin; is under close observation and currently doing well. It is empirical to report case reports, specifically unusual cases like OS of the skull. Case reports not only help disseminate knowledge but also help streamline diagnostic and treatment approaches for unusual cases.